(untitled) (CAHIERS MAGELLANES-NS, 2024)
The conflict between what language learners find in the educational environment of English language schools and the educational teachings of the family, television, and schools erodes morals and social norms. The current research investigates the foreign language teaching and the transfer of cultural values ​​of the source society: a case study of English language teaching. It is an applied survey. Its statistical population includes teachers and students of English language schools. Four questionnaires were planned for the implementation of this project. The first questionnaire was associated with language learners younger (up to 18 years old). The second was for adult language learners (over 18 years old), the third was for teachers, and the fourth questionnaire was for the status of institutions. The validity of the questionnaires was investigated through its experimental implementation on a small sample. The validity of the questionnaires was examined by the opinions of at least 5 other experts. As the results showed, most of the teachers confirmed the lack of attention in the textbooks to spiritual and religious issues and evaluated it much less than the average level. Likewise, the equal view of different cultures and civilizations of the world in educational books is also another critique by them. 5% of the teachers have overestimated the influence of the cultural concepts and contents of English language teaching resources on language learners, and 18% of them have considered this influence to be insignificant. An interview with the language learners also showed that religious subjects do not create much interest among them for education, but subjects on the lifestyle in the West and what show the difference between life in Iran and the West are among the subjects of interest for language learners.